Chaotic Characteristic Verification of Gearbox Vibration Signal based on the Time Synchronous Averaging and Separation Technology - Li Jie; Zhao Jianmin (Jixie chuandong)
The gearbox vibration signal of normal and different degrees teeth break fault condition are analyzed,the chaotic characteristics of the gearbox vibration signal are verified by using the time synchronous averaging method（ TSA） to separate the linear components in the vibration signal of the gearbox and the remaining nonlinear components as the research object. The results show,the chaotic characteristic of gearbox degeneration can be effectively extracted,the existence of chaos in the vibration signal of gearbox is verified in the life-time run.